EMPOWERMENT VISIONARY LEADERSHIP AND JOB SATISFACTION TO IMPROVE TEACHER CREATIVITY - Peni Apriyani; Entis Sutisna; Henny Suharyati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
This study examines the improvement of teacher creativity which is driven by the visionary leadership strength of the principal and teacher job satisfaction. The survey method with the correlational approach was used in this study to describe the strong relationship between teacher creativity as the dependent variable with the visionary leadership of the principal and teacher satisfaction as an independent variable. The population in this study were all permanent teachers of foundationÂ  Private Vocational High Schools in Parungkuda Sukabumi District. Samples were taken using a proportional random sampling technique totaling 96 teachers. The data analysis technique of the research results consisted of the first, statistical description and the second by using inferential statistics to test the hypothesis. The results showed that: (1) there was a very significant positive relationship between Principal Visionary Leadership and Teacher Creativity with a simple linear regression equation Å¶ = 89.33 + 0.32 X1 and the correlation coefficient value ry.1 = 0.217. The coefficient of determination r2y.1 = 0.217 means that the Visionary Leadership of the Principal (X1) contributes to the teacher's creativity by 16.50%; (2) there is a very significant positive relationship between Job Satisfaction with teacher creativity with a simple linear regression equation Å¶ = 88.48 + 0.31 X2 and the correlation coefficient ry.2 = 0.319, and the coefficient of determination r2y.2 = 0.122 which means that the contribution of Job Satisfaction (X2) to the creativity of teachers is 20.46%. (3) there is a very significant positive relationship between Principal Visionary Leadership and Job Satisfaction together with teacher creativity with multiple linear regression equations 88 = 77.25 + 0.21 X1 + 0.12 X2 and the value of the correlation coefficient ry. 12 = 0.165. The coefficient of determination r2y.12 = 0.390 means that the Visionary Leadership of the Principal (X1) and Job Satisfaction (X2) jointly contribute to the teacher's Creativity (Y) of 21.70%.